Inhibition of the CDK2 and Cyclin A complex leads to autophagic degradation of CDK2 in cancer cells - Jiawei Zhang; Yichao Gan; Hongzhi Li; Jie Yin; Xin He; Liming Lin; Senlin Xu; Zhipeng Fang; Byung-wook Kim; Lina Gao; Lili Ding; Eryun Zhang; et al. (Nature Communications, 2022)
CDK2 can drive the proliferation of cancer cells. Here, the authors screened for a non-ATP competitive inhibitor of the CDK2/cylinA complex and find that Homoharringtonine can disrupt the complex and promote the degradation of CDK2.